Catalysis in Solid Hydrogen Storage: Recent Advances, Challenges, and Perspectives. Issue 9 (28th July 2022) - Salman, Muhammad Saad; Pratthana, Chulaluck; Lai, Qiwen; Wang, Ting; Rambhujun, Nigel; Srivastava, Kshitij; Aguey-Zinsou, Kondo-Francois
Abstract : Catalysis is at the core of previous energy transition. It has enabled the use of oil and natural gas as our primary energy sources in unprecedented ways and led to feedstocks enabling exceptionally high living standards in human history. In a decarbonized economy with hydrogen as the new energy vector, catalysis is already playing a key role in producing hydrogen. However, catalysts for the effective storage of hydrogen must be advanced. Many solid hydrogen storage materials such as magnesium‐based hydrides, alanates, and/or borohydrides display promising hydrogen densities far superior to the current state of compressed or liquid hydrogen. These solid materials have thermodynamic and kinetic barriers which severely hinder their practical hydrogen uptake and release. To date, most of these barriers for solid hydrides (especially boron or nitrogen compounds) are modified via catalysis; however, the catalytic species per se and their roles are obscure. Herein, a comprehensive overview of various catalysts for solid hydrogen storage materials, their catalytic roles, and the underpinning mechanisms is provided. The current state of knowledge is critically reviewed and gaps where further research intensification is needed to support rapid hydrogen generation and storage in solid materials for the emerging hydrogen economy are identified. Abstract : Catalysis is core to all steps of solid‐state hydrogen storage.